SCREENING OF ANTI-OXIDANT POTENTIAL OF AQUEOUS EXTRACT OF CRATAEVA RELIGIOSA AGAINST PARACETAMOL INDUCED HEPATOTOXICITY IN WISTAR RATS - C.M. Jaikanth; K.V. Venkateswaran; S. Selvasubramanian; P.S.L. Sesh (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was taken up to evaluate the antioxidant potential of aqueous extracts of Crataeva religiosa in paracetamol induced hepatotoxicity in rats and also to compare their effects with the standard drug, silymarin. Twenty four female Wistar rats were used for the study. Toxicity was induced on day one in all the animals with an oral acute toxic dose of paracetamol at the rate of 3g/kg bw. Treatments with standard drug (silymarin at 100 mg/kg bw.) and test drug (aqueous extract of C. religiosa at 200 and 400 mg/kg bw.) were given from day 2 to day 8. Both the standard and test drugs exhibited a significant effect in restoring the altered antioxidant parameters in the liver. The aqueous extract at 400 mg/kg bw. excelled better than the dose of 200 mg/kg bw. in restoring the antioxidant parameters.